Key to families of the polydesmid order (Diplopoda, Polydesmida) in Vietnam - Anh, Nguyen Duc; Thanh Binh, Tran Thi (Academia Journal of Biology, 2006)
The paper presents the key to families of the Polydesmid order (Diplopoda, Polydesmida) in Vietnam. Currently, 6 Polydesmid families including Platyrhacidae, Paradoxosomatidae, Cryptodesmidae, Pyrgodesmidae, Opisotretidae and Doratodesmidae have been recorded in Vietnam. The paper also gives informations of the ecological features and the distribution of these families. Key to families of Polydesmida in Vietnam 1 (2) Body much larger (more than 60 mm long, more than 7 mm wide). Epiproct large, spoon-or shovel- shaped ………………………………………………………………………...…….. 1. Platyrhacidae 2. (1) Body smaller (less than 60 mm long, less than 7 mm wide). Epiproct smaller and other shaped. 3. (4) The paraterga of second segment set lower than that of third segment and lateral end of collum. Setae on paraproct far from lateral margin of anus …………………………….….  .2. Paradoxosomatidae 4. (3) The paraterga of second segment set equally or higher than that of third segment and lateral end of collum. Setae on paraproct close to lateral margin of anus. 5. (8) Body flat. Collum enlarged, covering most or all of head in dorsal view, its anterior edge incisied or lobed. Paraterga long, like wing of airplane. 6. (7) Paraterga subtriangular, gradually tapering towards the top. Lateral side usually incised into lobes or serrulated ………………………………………………………………….…...... .3. Cryptodesmidae 7. (6) Paraterga broad, horizontal, rectangular, not tapering towards the top. Lateral side of paraterga only incised…………………………………………………………………………….   4. Pyrgodesmidae 8. (5) Body cylindrical. Collum not enlarged, not cover the head in dorsal view, its anterior edge never incised. Paraterga short, small. 9. (10) Metaterga with three transverse rows of setae, each row with 4 setae organized as 2 + 2……………………………………………………………………………….……  .5. Opisotretidae 10. (9) Metaterga only with a dorsal, very big tubercle ……………………………….     6. Doratodesmidae